2021
DOI: 10.1186/s43045-021-00089-6
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and its risk factors during COVID-19 pandemic in Saudi Arabia: a cross-sectional study

Abstract: Background The control measures during COVID-19 such as curfew, lockdown, and social distancing had observed differences in controlling the spread of the disease around the Kingdom of Saudi Arabia; however, they might contribute to psychological illnesses such as anxiety, depression, panic disorder, and distress. A cross-sectional descriptive study was conducted to assess psychological distress and the factors affecting it among general population in the Kingdom of Saudi Arabia during the COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 21 publications
8
15
2
Order By: Relevance
“…The prevalence in the current study is comparable with a Chinese study, which found 54%, 16 and higher than studies from Italy and Saudi Arabiac, which were 38% and 35%, respectively. 24,25 The higher prevalence in our study could be attributed to differences in study populations: the Italian and Saudi Arabian studies were conducted among the general population, but ours was conducted among hospitalized patients. The variation might also be related to differences in the health-care structures anddelivery systems.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The prevalence in the current study is comparable with a Chinese study, which found 54%, 16 and higher than studies from Italy and Saudi Arabiac, which were 38% and 35%, respectively. 24,25 The higher prevalence in our study could be attributed to differences in study populations: the Italian and Saudi Arabian studies were conducted among the general population, but ours was conducted among hospitalized patients. The variation might also be related to differences in the health-care structures anddelivery systems.…”
Section: Discussionmentioning
confidence: 69%
“…Univariate logistic regression analysis of education status, living in an urban setting, female sex, marital status, perceived life threat, history of mental illness, childhood trauma, current alcohol use, poor social support, current khat use, and current cigarette use yielded P<0. 25. As such, these variables fulfilled the minimum requirement for multivariate binary logistic regression analysis (Table 4).…”
Section: Factors Associated With Psychological Distressmentioning
confidence: 89%
“…4,5,27,29 In this study, we found that being single is correlated with higher levels of stress, which is similar to earlier studies that reported a higher level of stress, anxiety and depression among singles during the pandemic in Saudi Arabia. 4,30 It was also evident that being single is a risk factor for distress, anxiety and depression in a metaanalysis conducted during the severe acute respiratory syndrome (SARS) outbreak. 31 In addition, it was found that having children was associated with lower levels of perceived stress.…”
Section: Only During Covid-19 Pandemic N (%)mentioning
confidence: 99%
“…However, one study in Saudi Arabia indicated that the prevalence rates of depression and general anxiety during the COVID-19 period were higher than the rates prior to the pandemic [ 10 ]. Furthermore, two studies conducted during the pandemic found that women in general had higher psychological distress than men in Saudi Arabia [ 11 , 12 ]. Therefore, our intention was to quantify levels of psychological distress among mothers and expectant mothers during the COVID-19 pandemic as a baseline reference for future research.…”
Section: Introductionmentioning
confidence: 99%